Ethylenediamine-NN'-tetra-acetate-dependent amino acid-stimulated inactivation of mouse ovarian alkaline phosphatase activity. - Bramley, T A (1975)
1. Preincubation of partially purified preparations of mouse ovarian alkaline phosphatase in the presence of both EDTA and glycine at alkaline pH resulted in a pronounced inactivation of alkaline phosphatase activity. Inactivation did not occur on preincubation with EDTA or glycine alone. 2. The rate of inactivation was first-order with respect to the concentration of enzyme, and was independent of EDTA concentration above a threshold value. 3. The process was pH-dependent with a pK at 9.85, and inactivation was not dependent on the stereochemistry of the amino acid. A free alpha-amino group and a free carboxyl group at a specific spatial separation were essential for inactivation. 4. Inactivation involved the formation of an enzyme--metal ion--amino acid complex, the amount formed being dependent on both the nature and concentration of the amino acid. This complex then decayed to a derivative that was then acted on by EDTA, yielding an inactive form of the enzyme.